A highly elastic conductive film prepared by bidirectional AS-LBL method. (5th January 2022) - Zhu, Pingwei; He, Zhichao; Liu, Siqi; Liu, Li; Huang, Yudong; Li, Jun
Graphical abstract: Highlights: Wrinkles allow films to cope with deformation while maintaining stable conductivity. The Ag NPs, MWCNTs and Ag-MWCNTs mixture are studied separately. During stretching, PU/Ag-MWCNTs show more stable conductivity than PU/Ag. During stretch cycle, Ag are easier to reconstruct the damaged conductive path. Abstract: Development of elastic conductive film is critical to prepare flexible electronic devices. Herein, bidirectional elastic conductive films based on polyurethane (PU) and different dimensional fillers were prepared by using an novel alternating stretching layer-by-layer self-assembly (AS-LBL) technology. It is shown that wrinkle structures were constructed in the conductive films, which allows them to cope with the deformation under bidirectional stretching to a certain extent, while maintaining stable conductivity. Basically, the one-dimensional MWCNTs exhibit the better construction speed of the conductive path than zero-dimensional Ag NPs. In addition, under the synergy of Ag NPs and MWCNTs, the conductivity of PU/Ag-MWCNTs films reaches the best. After adsorbing 6 layers of Ag-MWCNTs, the conductivity of the film increased to 0.24 S cm −1 . More importantly, during the stretching process, the PU/MWCNTs and PU/Ag-MWCNTs films show a more stable conductivity than PU/Ag. As the strain increases from 0 to 500%, the conductivity of PU/Ag-MWCNTs films decreases by only 9.6%. However, during the stretch-release cycle, the zero-dimensional small-sized Ag NPs display a more superior ability of conductive path reconstruction than MWCNTs. When the elongation is 100%, after 100 stretching cycles, the conductivity of PU/Ag film is only reduced by 8%.